The Impact of Technological Innovation on Energy Intensity: Evidence from Indonesia - Saudi, Mohd Haizam Mohd; Sinaga, Obsatar; Roespinoedji, Djoko; Ghani, Erlane K. (International Journal of Energy Economics and Policy, 2019)
The present study not only focuses on single measure of technological innovation but included three core dynamics of measuring technological innovations. These include Research and Development expenditures, High-tech exports and patents by residents. This kind of extensive examination will provide greater understanding regarding which form of technological innovation have the tendency to curtail or augment levels of energy intensity in Indonesia. The awareness derived from such broad inspection would be able to identify not only the overall contribution of technological innovations in affecting country’s power intensity but highlight the specific role of each form of innovation in influencing energy intensity levels and the particular association to guide effective policy making process. The current study has adopted the refined methodology of Auto-Regressive Distributed Lags (ARDL) bound testing approach to examine the dynamic relationship among energy intensity and technology innovation with amplified understanding of the critical association to support the course of economic planning and policy making. The results of ARDL bound testing approach confirm that high technology exports, research and development expenditure and number of registered patents are strong determinants of energy inefficiency in Indonesia. Likewise, the outcomes affirm that all the three proxies of technology innovation have a constructive and negative effect on energy inefficiency in Indonesia which implies that the high technology exports, number of registered patents and R&D expenditure are the main source of reducing energy inefficiency in Indonesia in the long run and short run. Also, the results of Granger causality method confirm a bi-directional causal relationship between energy intensity and technology innovation in Indonesia. Keywords: Energy intensity, technology innovation, R&D, Indonesia. JEL Classifications: Q4, O3 DOI: https://doi.org/10.32479/ijeep.7731